The impact of the 2008 crisis on foreign direct investments: Panel tobit approach - (:unkn) unknown (International Economic Society, 2015)
Since 1990 foreign direct investment (FDI) flows have shown a significant increase both in developed and developing countries. Before the financial crisis in 2008, which affected the whole world, they had reached their highest level. Due to FDI, not only finance but also advanced technology and new industry are being provided in developing countries. Even though the 2008 crisis caused a significant global decrease of FDI, the impact of the crisis on developing and developed economies has been different. The aim of this study is to analyze the impact of the 2008 crisis on the FDI of developed, developing and undeveloped countries, and to identify the macroeconomic factors affecting FDI. In order to see the impact of the crisis on FDI in the period 2005-2011 according to the development levels of the countries panel Tobit models were estimated, and in order to analyze in detail the factors affecting FDI before, during and after the crisis according to the development level, separate cross-section Tobit models for every year were estimated. The Tobit models estimated separately for every year with the help of the cross section data thus it was possible to indicate in detail which of the variables taking place in the panel Tobit models according to the development levels were effective on FDI before and after the crisis and which ones during the crisis. The results of the estimated models have shown that the most influential factor on FDI in all the development levels is the current account balance. © International Economic Society.
Keywords: Cross sectional models; Foreign direct investment; Panel tobit model; Tobit model